Tyrosine phosphatase SHP2 regulates the expression of acyl-CoA synthetase ACSL4 - Cooke, Mariana (2011)
Acyl-CoA synthetase 4 (ACSL4) is implicated in fatty acid metabolism with marked preference for arachidonic acid (AA). ACSL4 plays crucial roles in physiological functions such as steroid synthesis and in pathological processes such as tumorigenesis. However, factors regulating ACSL4 mRNA and/or protein levels are not fully described. Because ACSL4 protein expression requires tyrosine phosphatase activity, in this study we aimed to identify the tyrosine phosphatase involved in ACSL4 expression. NSC87877, a specific inhibitor of the tyrosine phosphatase SHP2, reduced ACSL4 protein levels in ACSL4-rich breast cancer cells and steroidogenic cells. Indeed, overexpression of an active form of SHP2 increased ACSL4 protein levels in MA-10 Leydig steroidogenic cells. SHP2 has to be activated through a cAMP-dependent pathway to exert its effect on ACSL4. The effects could be specifically attributed to SHP2 because knockdown of the phosphatase reduced ACSL4 mRNA and protein levels. Through the action on ACSL4 protein levels, SHP2 affected AA-CoA production and metabolism and, finally, the steroidogenic capacity of MA-10 cells: overexpression (or knockdown) of SHP2 led to increased (or decreased) steroid production. We describe for the first time the involvement of SHP2 activity in the regulation of the expression of the fatty acid-metabolizing enzyme ACSL4.